Prevalence and factors associated to dysphonia and laryngeal lesions: a study among teachers in a region of the Brazilian Legal Amazon - Cruz, Fernanda Aguiar da; Rêgo, Adriana Sousa; Firmo, Wellyson da Cunha Araújo; Bassi-Dibai, Daniela; Silva, Flor de Maria Araujo Mendonça; Silva, Ilana Mírian Almeida Felipe da (Revista de Ciências Médicas e Biológicas, 2021)
Objective: to investigate the prevalence and factors associated with dysphonia and laryngeal lesions in teachers of basic education in a region of the Amazonian region. Methods: cross-sectional study with collection of sociodemographic variables, occupational, environmental and clinics. Laryngeal lesions were evaluated by laryngoscopy. Was used a logistic regression to determine factors associated. Results: the prevalence of dysphonia and laryngeal lesions was 68.9% and 53.3%, respectively. There was association between self-reported dysphonia and respiratory problems (OR=3.00; CI95%=1.25-7.22), use of drugs (OR= 2.31, CI95%= 1.19-4.49) and noise in the internal environment (OR= 2.43; CI95%=1.24-4.73). Easy access to water was a protection factor against self-reported dysphonia (OR=0.09; CI95%: 0.01-0.79). We found a significant association between dysphonia diagnosed and digestive problems (OR= 6.09; CI95%=2.79-13.30), external noise (OR=5.20, CI95%=1.99-13.57) and inadequate ventilation (OR=3.24; CI95%=1.36-7.74). The variables associated with higher chance of laryngeal lesions in dysphonic teachers were lighting (OR=3.74; CI95%=1.15-12.14%), acoustics (OR= 4.14; CI95%=1.32-12.95) and inadequate room size (OR= 3.76; CI95%=1.29-10.91). The use of drugs (OR=0.34; CI95%=0.12-0.92), respiratory problems (OR=0.21; CI95%=0.06-0.76) and easy access to water (OR= 0.12; CI95%=0.04-0.38) were protection factors for laryngeal lesions. Conclusion: occupational environmental factors aggravated the vocal health of this professional category. Access to water in the work impacted positively.